Integration of 21st Century Skills into Islamic Religious Education Learning Methods - Satri Handayani; Neni Neni; Sulthon Fathoni (SYAMIL: Journal of Islamic Education, 2025)
Integration of 21st Century Skills into learning methods is crucial in modernizing Islamic Religious Education (PAI), particularly to address the challenges of learning that are relevant to the demands of the times. This study bridges the gap between traditional Islamic pedagogy and 21st-century competencies, focusing on the material of QS. Al Hujurat: 13. This study uses a qualitative descriptive approach with data collected through in-depth interviews with four PAI teachers from four Public Elementary Schools in Garo City, who were purposively selected based on their active involvement in teaching PAI and their experience implementing 21st-century learning strategies. Interviews were conducted during March–April 2025, recorded, transcribed, and analyzed using Miles and Huberman's interactive analysis model which includes data reduction, data presentation, and drawing conclusions. The results show that PAI teachers apply active learning methods such as group discussions, project-based learning, and the use of digital media, with the main challenges being limited learning time, lack of supporting facilities, and minimal teacher training, while existing support includes school policies and collaboration between teachers. These findings confirm that integrating 21st-century skills into Islamic Religious Education (PAI) learning can increase student engagement and material relevance, but requires adaptive strategies to address resource constraints. This study contributes theoretically by offering a framework for integrating 21st-century competencies into Islamic Religious Education (PAI) learning and practically by providing recommendations for teacher training and strengthening systemic support.